Rule-of-Law Crisis During the COVID-19 Epidemic: The Case of Slovenia - Kogovšek Šalamon, Neža (Medicine, Law & Society, 2025)
This article examines the Constitutional Court of Slovenia's rulings on the government's COVID-19 measures between 2020 and 2022. During the pandemic, the Slovenian government imposed lockdowns, curfews, and school and business closures, and required a "COVID pass" for access to services. These restrictions significantly interfered with fundamental rights, leading to numerous legal challenges. The Constitutional Court found several of these decrees unconstitutional, revealing serious tensions between public health governance and constitutional democracy. The article has two main goals: to evaluate the extent of rights violations and to assess whether rule-by-decree is aligned with democratic principles. The findings show that the rule of law was often undermined, with pandemic-related legal tools at times used to pursue authoritarian political aims. Slovenia's case demonstrates the fragility of democratic institutions in emergencies. It highlights the vital role of constitutional courts in defending the constitutional order, especially when they themselves face political attacks in increasingly illiberal environments.